Laser ablation-tandem ICP-mass spectrometry (LA-ICP-MS/MS) imaging of iron oxide nanoparticles in Ca-rich gelatin microspheres. Issue 9 (10th July 2019) - Van Acker, Thibaut; Bolea-Fernandez, Eduardo; De Vlieghere, Elly; Gao, Jingxian; De Wever, Olivier; Vanhaecke, Frank
Abstract : A new analytical method for quantitative high-resolution LA-ICP-MS/MS imaging of FeO x NPs in gelatin microspheres. Abstract : This work describes the development of an analytical method for quantitative laser ablation tandem ICP-mass spectrometry (LA-ICP-MS/MS) imaging of iron oxide nanoparticles (FeO x NPs) in gelatin microspheres containing CaCO3 crystals (≤30 μm diameter). The strong spectral overlap between the signal of 56 Fe + and those of 40 Ar 16 O +, 38 Ar 18 O +, 40 Ar 15 NH + and 40 Ca 16 O + and between those of 40 Ca + and 40 Ar + was overcome by relying on chemical resolution using a mixture of NH3 /He (1 : 9) in a mass-shift approach. Product ion scanning allowed Fe(NH3 )2 + and CaNH3 + to be identified as the best suited reaction product ions, formed upon reaction of NH3 with Fe + and Ca +, respectively. The method was validated by using two certified reference materials, i.e. NIST SRM 1577 and 1577a bovine liver, which were solubilized by acidic digestion. Fe-spiked gelatin droplet standards were prepared on a high-purity single-side polished silicon wafer and used as external calibration standards for LA-ICP-MS/MS analysis and a priori, their corresponding Fe concentrations were determined via pneumatic nebulization tandem ICP-MS (PN-ICP-MS/MS) after acidic digestion. High-resolution LA-ICP-MS/MS imaging revealed the mixed structure of the gelatin microspheres containing a high loading of FeO x NPs (2.69 ± 0.91 wt% Fe) in the gelatin phase. The high FeO x NP concentrations are required for magnetic removal after peritoneal injection and are accompanied by numerous CaCO3 crystals that provide an indication about the final porosity of the microspheres.